AMAP Assessment 2013: Arctic Ocean Acidification. - Arctic Monitoring and Assessment Programme (AMAP) (Arctic Monitoring and Assessment Programme (AMAP), 2013)
"This assessment report presents the results of the 2013 AMAP Assessment of Arctic Ocean Acidification (AOA). This is the first such assessment dealing with AOA from an Arctic-wide perspective, and complements several assessments that AMAP has delivered over the past ten years concerning the effects of climate change on Arctic ecosystems and people." Norway, Canada, Sweden, USA, the Nordic Council of Ministers